Association between cytochrome P450 2D6 polymorphisms and body fluid methamphetamine concentrations in Japanese forensic autopsy cases - Matsusue, Aya; Ikeda, Tomoya; Tani, Naoto; Waters, Brian; Hara, Kenji; Kashiwagi, Masayuki; Takayama, Mio; Ikematsu, Natsuki; Kubo, Shin-ichi; Ishikawa, Takaki (Forensic science international, 2018)
•CYP2D6 phenotypes were identified in methamphetamine (MA) abusers and controls.•MA and amphetamine (AMP) levels were measured in body fluids from MA abusers.•MA levels in urine and bone marrow were significantly higher in IM than in EM.•CYP2D6 phenotypes were not correlated with AMP concentrations in body fluids. Methamphetamine (MA) is an illicit stimulant that affects the central nervous system. Cytochrome P450 2D6 (CYP2D6) plays an important role in MA metabolism. Numerous allelic variants confer substantial variation in CYP2D6 activity among individuals. In the present study, we examined the frequencies of CYP2D6 alleles, including CYP2D6*1, *2, *4, *5, *10, *14A, *14B, *18, and *36, and multiplication, in 82 forensic autopsy cases of MA abusers and 567 autopsy cases in which MA was not detected (controls). Ultrarapid metabolizer (UM), extensive metabolizer (EM), intermediate metabolizer (IM), and poor metabolizer (PM) phenotypes were predicted from CYP2D6 genotypes. Of MA abusers, 64 subjects were predicted to be EM, 17 were IM, and 1 was UM. No MA abuser had the predicted PM phenotype. No significant differences in CYP2D6 phenotype frequencies were found between MA abusers and controls. MA and amphetamine (AMP) concentrations were measured in the right heart blood, left heart blood, peripheral external iliac blood, urine, pericardial fluid, and bone marrow of MA abusers. MA concentrations in urine and bone marrow were significantly higher in IM than in EM. AMP concentration was not associated with CYP2D6 phenotype in any body fluid. These results suggest that the MA concentration in body fluids is influenced by CYP2D6 phenotypes in the Japanese population.